2022
DOI: 10.31603/bphr.v2i1.7060
|View full text |Cite
|
Sign up to set email alerts
|

Formulasi sediaan lip cream ekstrak buah naga merah (Hylocereus polyrhizus) sebagai pewarna alami

Abstract: Latar Belakang : Lip Cream adalah sediaan kosmetik yang digunakan untuk mewarnai bibir dengan sentuhan artistik sehingga dapat meningkatkan nilai estetika dalam tata rias wajah. Salah satu contoh yang dapat dijadikan pewarna alami adalah buah naga merah (Hylocereus polyrhizus) karena mengandung pigmen antosianin yang berfungsi sebagai pigmen warna. Tujuan : Untuk mengetahui ekstrak buah naga merah (Hylocereus polyrhizus) sebagai pewarna alami dapat diformulasikan dalam sediaan lip cream. Metode : Penelitian di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…The homogeneity test results showed that the nanoemulsion lipcream preparation had no coarse grains when applied to the glass object and the color was even. The conventional lip cream preparations F1 and F2 showed that there were coarse grains that were not homogeneous when applied to a glass object and the color of the secang wood extract was uneven 18 . Nanoemulsion lip cream preparations are said to be more homogeneous because the process of making secang wood extract with a homogeneous and stable nanoemulsion base, whereas conventional lip cream preparations of secang wood extract are directly included in the lip cream base.…”
Section: Resultsmentioning
confidence: 99%
“…The homogeneity test results showed that the nanoemulsion lipcream preparation had no coarse grains when applied to the glass object and the color was even. The conventional lip cream preparations F1 and F2 showed that there were coarse grains that were not homogeneous when applied to a glass object and the color of the secang wood extract was uneven 18 . Nanoemulsion lip cream preparations are said to be more homogeneous because the process of making secang wood extract with a homogeneous and stable nanoemulsion base, whereas conventional lip cream preparations of secang wood extract are directly included in the lip cream base.…”
Section: Resultsmentioning
confidence: 99%
“…Kosmetika adalah sediaan atau paduan bahan yang siap untuk digunakan pada bagian luar badan (epidermis, rambut, kuku,bibir, dan organ kelamin bagian luar), gigi, dan rongga mulut untuk membersihkan, menambah daya tarik, mengubah penampakan, melindungi supaya tetap dalam keadaan baik, memperbaiki bau badan tetapi tidak dimaksudkan untuk mengobati atau menyembuhkan suatu penyakit. Kosmetika dekoratif semata-mata hanya melekat pada alat tubuh yang dirias dan tidak bermaksud untuk diserap kedalam kulit serta mengubah secara permanen kekurangan (cacat) yang ada (Utami, 2019).…”
Section: Pembahasanunclassified